Financial Performance And Sharia Compliance: Evidence From Sharia Bank In Indonesia - Kurnia, Rahmat; Zilal Afwa Ajidin; Rakotoarisoa Maminirina Fenitra; Putra, Gusti Dirga Alfakhri; Manan, Farah Nadirah Abdul (LPPM ISNJ Bengkalis, 2025)
This research aims to describe the development of Islamic banks in Indonesia based on the Shariah Compliance and Profitability (SCnP) approach from 2018 to 2022. Quantitative descriptive panel data analysis was used as a research method, with purposive sampling of 10 Islamic banks in Indonesia. Islamic commercial banks are used as a testing method. The financial performance of Islamic banks is measured using two approaches, namely sharia (profit sharing ratio, sharia public investment ratio, sharia income ratio) and profitability indicators (return on assets, return on equity, net profit margin) . The average financial performance condition of Islamic banks in Indonesia as a whole shows performance in four quadrants, namely Upper Right Quadrant (URQ), Lower Right Quadrant (LRQ), Lower Left Quadrant (LLQ), Upper Left Quadrant (ULQ) in the five periods. each bank per year.